Optimization of Deep Oxidative Desulfurization Process Using Ionic Liquid and Potassium Monopersulfate - Yinke Zhang; Hang Xu; Mengfan Jia; Zhuang Liu; Deqiang Qu (Journal of Chemistry)
Response surface methodology (RSM) was selected to optimize a desulfurization process with metal based ionic liquids ([Bmim]Cl/CoCl2) and potassium monopersulfate (PMS) together to remove benzothiophene (BT) from octane (simulating oil). The four experimental conditions of PMS dosage, [Bmim]Cl/CoCl2 dosage, temperature, and reaction time were investigated. The results showed that the quadratic relationship was built up between BT removal and four experimental variables with 0.9898 fitting coefficient. The optimal conditions were 1.6 g (20 wt%) PMS solution, 3.2 g [Bmim]Cl/CoCl2, 46°C, and 23 min, which were obtained based on RSM and experimental results. Under the optimal condition, predicted sulfur removal rate and experimental sulfur removal rate were 96.7% and 95.4%, respectively. The sequence of four experimental conditions on desulfurization followed the order temperature > time > [Bmim]Cl/CoCl2 dosage > PMS solution dosage.